The Implementation of Literacy Culture Programs in Elementary School - Vevy Liansari; Wahyu Taufiq; Dian Rahma Santoso (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to describe the implementation of literacy culture programs of elementary school. This study used phenomenology of a qualitative approach. The subjects were the headmaster, teachers, students who were selected by using purposive sampling technique. The validity data test used triangulation techniques by comparing the results of observations, interviews, and documentation. The results showed that: 1) The policy for implementing a literacy culture at elementary school by using the School Literacy Movement program of the government. It is based on Permendikbud No. 23, 2015 focusing on character development. (2) The implementation of literacy culture of elementary school. It is based on the habituation stage that carried out 10 minutes of reading Al Qur’an and storybooks before lessons. The development stage of the activities carried out the respond to the contents of reading books by reading independently, giving appreciation for student literacy achievements, and having a school literacy team. The learning stage is by getting used to reading textbooks and using various strategies that support learning.